Quality-adjusted Life Years and Costs of Mechanical Thrombectomy for Very Elderly Patients with Acute Ischaemic Stroke - Takeshi INABA; Mio SAKUMA; Fumihiro SAKAKIBARA; Kazutaka UCHIDA; Takeshi MORIMOTO (Neurologia Medico-Chirurgica)
This study aimed to evaluate the cost-effectiveness of mechanical thrombectomy (MT) in patients aged 90 years and older with acute ischaemic stroke (AIS). We developed a cost-effectiveness model to compare MT with standard medical care (SMC) to SMC alone. The model, incorporating parameters for the effectiveness and costs of MT with SMC and SMC alone, was simulated until the cohort reached 100 years of age. The parameters were estimated from the prospective cohort study of the RESCUE-Japan Registry 2, claims databases, and published literature, with the perspective being Japan's public healthcare system. In the base-case model for an 8-year simulation period, the quality-adjusted life years (QALYs) for MT with SMC and SMC alone were 1.463 and 1.054 years, respectively. The expected costs were 14,553,772 Yen and 13,732,646 Yen, respectively. The incremental cost-effectiveness ratio (ICER) of MT with SMC compared to SMC alone was 2,009,744 Yen per QALY. A probabilistic sensitivity analysis showed a 66% probability that MT with SMC would be below the ICER threshold of 5,000,000 Yen per QALY. The cost-effectiveness analyses demonstrated that performing MT in addition to SMC for AIS in patients aged 90 years and older was acceptable from a cost-effectiveness perspective.